Taxonomic assessment of insect pollinators in agricultural landscapes (Zoological Records and Reviews, 2022)
Insect pollinators provide essential ecosystem services underpinning global food security, yet agricultural intensificationhas driven severe declines in pollinator diversity and abundance across Europe and beyond. Accurate taxonomicassessment of pollinator communities in agricultural landscapes is fundamental to understanding the drivers of pollinatordecline and designing effective conservation interventions, yet many agri-environment monitoring programmes rely oncoarse functional group classifications rather than species-level identification. This study presents a comprehensivetaxonomic assessment of insect pollinators across three agricultural landscape types -- intensive arable, mixed farming,and organic arable -- in southwestern France, northeastern Spain, and southern Sweden, using standardised pan-trapand transect survey methods over two growing seasons (2019-2020). A total of 312 pollinator species from 7 orders and42 families were documented, comprising 148 bee species (Hymenoptera: Apoidea), 84 hoverfly species (Diptera:Syrphidae), 46 butterfly species (Lepidoptera: Papilionoidea), and 34 species from other pollinator groups. Speciesrichness was 47.3% higher in organic compared to intensive arable landscapes (p < 0.001). Floral resource diversity,semi-natural habitat cover, and pesticide application frequency were identified as the strongest predictors of pollinatorspecies richness. Rare and specialist pollinator species were disproportionately associated with field margins containingdiverse native wildflower communities. Agri-environment scheme effectiveness varied substantially by pollinatortaxonomic group, with hoverflies and solitary bees showing the greatest response to wildflower margin interventions.
Keywords: pollinator decline; pesticide impact; wildflower margins; taxonomic assessment; species richness; agri-environment schemes; hoverflies; bee diversity; agricultural landscapes; insect pollinators